Investigating the impacts of H2O2 treatment on gills of healthy Atlantic salmon reveals potential changes to mucus production with implications on immune activity. Issue 128 (September 2022) - Fernandez-Senac, Carolina; Monaghan, Sean J.; Mascolo, Dario; Baily, Johanna L.; Betancor, Monica; Chalmers, Lynn; Paladini, Giuseppe; Adams, Alexandra; Fridman, Sophie; Bron, James E.
Abstract: Current treatment strategies for relevant infectious diseases in Atlantic salmon ( Salmo salar L.) include the use of low salinity or freshwater bathing. However, often availability is restricted, and hydrogen peroxide (H2 O2 ) is used as an alternative. The potential impacts of H2 O2 on fish mucosal tissues, especially the gills therefore need to be considered. In this study the mucosal and immunological effects of H2 O2 treatment on the gills of healthy Atlantic salmon were examined by gene expression (qPCR) and immunohistochemistry (IHC) investigating T-cell, B-cell, and mucin activity. Healthy fish were treated with H2 O2 and sampled at different times: 4 h, 24 h and 14 days post-H2 O2 treatment (dpt) (total n = 18) to investigate the effect of holding time and H2 O2 treatment. Treatment with H2 O2 resulted in up-regulation of markers for T-cell activity and anti-inflammatory response and down-regulation of mucin expression in the gills at 14 dpt compared to fish sampled prior to treatment (0h; n = 5 fish). These findings were supported by IHC analysis, which despite being highly variable between samples, showed an increase in the number of CD3 + T cells at 14 dpt in 50% of treated fish compared to pre-treatment fish. The results from this study suggest that H2 O2 treatment does not immune compromise healthy Atlantic salmon after 14 dpt ( i.e., post-recovery) but modulates gill immune activity and disrupts the mucus covering of the gills. However, further studies are required to determine whether the effects observed are related to H2 O2 treatment in isolation or other variables such as holding time or environmental factors. Highlights: Immunohistochemistry and gene expression analysis showed immunological activity in healthy gills from holding time in the presence of H2 O2 effects of hydrogen peroxide. Protective mucosal coat disruption was observed on the gills of healthy Atlantic salmon after 14 days of exposure to hydrogen peroxide. Reduction of mucus production due to lower number of mucous cells after 14 days of exposure to hydrogen peroxide could explain the up-regulation of some immune genes related to cell infiltration.